Routledge international handbook of sexual homicide studies - Proulx, Jean; Beauregard, Eric; Carter, Adam J.; Mokros, Andreas (Routledge International Handbooks, 2018)
"This book provides the first systematic overview of the theoretical, empirical, clinical, and police issues related to sexual murderers and murder. Bringing together leading researchers, theoreticians, and practitioners from across eight different countries, this is a truly international collaboration and an essential reference text for students, researchers, and professionals interested in sexual homicide, as well as an exhaustive source of guidelines for the assessment and treatment of sexual murderers. This book is divided into five parts:Part I, Theories and research, presents a detailed review of theoretical models and empirical studies of sexual homicide. Part II, Sexual sadism, discusses theoretical, empirical, and clinical considerations and reviews the literature on the characteristics of sadistic sexual aggressors. Part III, Clinical issues, discusses the assessment and management of sexual murderers at each phase of the judicial process: at trial, during incarceration, and during follow-up in the community. Part IV, Policing issues, discusses research and practical issues related to police activities surrounding a sexual murder. Topics include investigation, offender and geographical profiling, behavioural linkage, and police interrogation of the murderers. Part V, New directions, presents new directions for the study of sexual homicide and discusses the limits of current knowledge related to sexual murderers and their crimes. Offering a broad and comprehensive approach, this Handbook is an indispensable source of information on theory, research, clinical assessment, treatment, and police issues related to sexual murderers and murder."--Provided by publisher